Orthodontic Treatment of Dental Open Bite in an Adult: A Case Report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Case report of an adult Bangladeshi male aged 26 years who complained about ineffective chewing of food and unpleasant aesthetic look. The patient was diagnosed to have a 4 mms of anterior dental open bite on skeletal Class I with normal mandibular plane and palatal plane angles. Treatment was orthodontics alone with non-extraction. The main mechanics used to close the anterior open bite, were by the conventional aligning, leveling and arch contraction by standard edgewise technique. The result showed that it was possible to correct the open bite within a short period; however, the appliance was difficult to clean. The treatment was complete after 2 years with positive overbite of 3 mms and acceptable occlusion. The patient was happy with his new appearance and function. DOI: http://dx.doi.org/10.3329/bjodfo.v1i1.15973 Ban J Orthod & Dentofac Orthop, October 2010; Vol-1, No.1, 16-21